_Not That Bad_: Lessons Women Learn in a Rape Culture - Sydney J Selman (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2022)
In 2018, Roxane Gay assembled an anthology that addresses the severity of rape, rejecting the common belief that some sexually violent acts, compared to others, are not that bad. This collection, titled Not That Bad: Dispatches from Rape Culture, compiles pieces from thirty different authors and sheds light on how the notion of not that bad contributes to a broader structural social problem involving sexual violence. This social problem, known as rape culture, is commonly defined as a culture that normalizes sexual violence and blames victims of sexual assault (“What is Rape Culture?”). In other words, rape culture trivializes sexual violence to a point at which victims “fear they won’t be believed—and know that even if they are believed, they’re likely to be mortified and harassed, blamed and shamed, throughout a legal process that ultimately leads nowhere” (Harding 1). Thus, understanding rape culture is critical for us as we begin to recognize just how bad rape really is. In this particular anthology, authors xTx and V. L. Seek recount their experiences with rape culture and the notion of not that bad, unveiling the distinct ways in which this culture is reproduced throughout childhood and within the legal education system. This paper uses the authors’ testimonies to guide our understanding of rape culture, and how it works to delegitimize victims to allow, if not encourage, rape.
Keywords: rape culture; rape; sexual assault; sexual violence; not that bad dispatches of rape culture; not that bad; rape and the law; law; the ways we are taught to be a girl; utmost resistance